EFFECTS OF CUSTOMER REVIEW, PRICE CUTS, QUALITY OF SERVICE AND SHOPPING LIFESTYLE ON IMPULSE BUYING - Syaiful Amri; Syaifuddin; Salman Faris; Sofiyan (Economic and Bussiness Faculty, Dr Soetomo University, 2024)
The research aimed to examine the effects of customer reviews, price cuts, service quality, and shopping lifestyle on impulse buying behavior in e-commerce environments. A Systematic Literature Review (SLR) was employed, using databases like Scopus, Web of Science, and Google Scholar to identify relevant studies. The methodology involved refining search strategies, applying inclusion and exclusion criteria, and screening studies using a PRISMA flowchart, which reduced 2471 initial records to 13 final studies for analysis. The results revealed that positive customer reviews act as social proof, enhancing trust and triggering impulsive purchases. Price cuts create urgency, which, when combined with positive reviews, further enhances perceived product value and impulsive buying. High-quality service contributes to consumer satisfaction, reducing perceived risks and encouraging spontaneous purchases. Shopping lifestyle, particularly among hedonic consumers, amplifies these effects, with digital natives being especially prone to impulsive behavior due to their convenience-driven and tech-savvy tendencies. The study concluded that customer reviews, price cuts, service quality, and shopping lifestyle interact synergistically, shaping consumer impulse buying behavior, with implications for e-commerce strategies aimed at increasing sales through these factors.